2018
DOI: 10.1002/sres.2563
|View full text |Cite
|
Sign up to set email alerts
|

Using a Stakeholder Analysis to Improve Systems Modelling of Health Issues: The Impact of Progesterone Therapy on Infant Mortality in Ohio

Abstract: Systems modelling of health issues enriches analysis of health care policies by exploring interdependencies among system components. Considering a wide range of stakeholder behavior is a requisite for developing a useful model. Our paper shows how to systematically identify stakeholder behavior, formulate them in a model and test their impact on health outcomes. Stakeholder behavior are explained in the context of a simulation‐based analysis of infant mortality in Ohio. Using group model building techniques, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Furthermore, our proposed coding process can be used for coding responses to other systems thinking vignettes. Group model building researchers and practitioners can also benefit from the proposed coding procedure to better elicit mental models of stakeholders based on textual data, utilize archival data, and validate their models (Andersen et al ., 1997; McCardle‐Keurentjes et al ., 2018; Hosseinichimeh et al ., 2019). We invite scholars of systems thinking, system dynamics, education, and complexity sciences to consider LUV as a tool and contribute to its further development, testing, and application.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our proposed coding process can be used for coding responses to other systems thinking vignettes. Group model building researchers and practitioners can also benefit from the proposed coding procedure to better elicit mental models of stakeholders based on textual data, utilize archival data, and validate their models (Andersen et al ., 1997; McCardle‐Keurentjes et al ., 2018; Hosseinichimeh et al ., 2019). We invite scholars of systems thinking, system dynamics, education, and complexity sciences to consider LUV as a tool and contribute to its further development, testing, and application.…”
Section: Resultsmentioning
confidence: 99%
“…Working collaboratively, however, the meaning of the TB IPC problem gravitated towards a 'common goal' re-emphasizing Zimmermann and Black's (2015) claim that the use of participatory methods can change meaning-or in our case could reshape perceptions of which evidence was seen as relevant. Hosseinichimeh et al (2019) suggest that a power-by-interest grid be completed by the modelling team to identify GMB participants to systematically determine a wider range of stakeholders; however, a way to navigate potential bias in attention to particular issues or concerns in the views that emerge during GMB workshops is still required. Despite this, as in other literature (Luna-Reyes et al, 2019;Martin, 2021;Morais et al, 2021), we found that the GMB workshops enabled discussion and debate between a variety of different stakeholders, and in turn, facilitated a greater understanding of problems identified and their associated solutions.…”
Section: Discussionmentioning
confidence: 99%
“…This stakeholder analysis aims to improve understandings of the unique programmatic and policy challenges and specific applications of technology in harm reduction settings. Stakeholder analyses have emerged as critical tools in policymaking, across political arenas and academic disciplines, and have become a particularly rich method within health policy research [23][24][25][26][27][28]. After agreeing to participate in the present study, stakeholders were interviewed either in person or over the telephone by two of the team's experienced qualitative researchers.…”
Section: Domains Of Inquirymentioning
confidence: 99%